1998
DOI: 10.1128/mcb.18.3.1163
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relationships of Srb10-Srb11 Kinase, Carboxy-Terminal Domain Kinase CTDK-I, and Transcriptional Corepressor Ssn6-Tup1

Abstract: The Srb10-Srb11 protein kinase of Saccharomyces cerevisiae is a cyclin-dependent kinase (cdk)-cyclin pair which has been found associated with the carboxy-terminal domain (CTD) of RNA polymerase II holoenzyme forms. Previous genetic findings implicated the Srb10-Srb11 kinase in transcriptional repression. Here we use synthetic promoters and LexA fusion proteins to test the requirement for Srb10-Srb11 in repression by Ssn6-Tup1, a global corepressor. We show that srb10⌬ and srb11⌬ mutations reduce repression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 78 publications
5
102
0
Order By: Relevance
“…As a consequence, overexpression of cell cycle cyclins usually generates growth defects (9,60,68). The CTDK-I complex is implicated not in cell cycle regulation but rather in transcription regulation (26,31). Similarly to what has been observed for other C-type cyclins implicated in transcription control, CTK2 mRNA levels do not fluctuate during the cell cycle (data not shown).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…As a consequence, overexpression of cell cycle cyclins usually generates growth defects (9,60,68). The CTDK-I complex is implicated not in cell cycle regulation but rather in transcription regulation (26,31). Similarly to what has been observed for other C-type cyclins implicated in transcription control, CTK2 mRNA levels do not fluctuate during the cell cycle (data not shown).…”
Section: Resultsmentioning
confidence: 53%
“…Deletion of any of the CTK genes generates cryosensitive cells. CTDK-I is related to the Srb10/11 kinase complex, although it seems to display a distinct role in transcriptional control (26). In vitro studies carried out with HeLa nuclear extracts have shown that CTDK-I can modulate the elongation efficiency of RNA polymerase II (31).…”
mentioning
confidence: 99%
“…One component, Srb10, a nonessential cyclin-dependent kinase, is part of a distinct Mediator-associated complex (the Srb8-11 complex) that interacts with Tup1 (Myer and Young, 1998;Zaman et al, 2001;Borggrefe et al, 2002). Srb10 has been shown to negatively affect transcription, and its kinase function is necessary for full repression of a Tup1-controlled reporter construct (Holstege et al, 1998;Kuchin and Carlson, 1998;Song and Carlson, 1998;Lee et al, 2000 DNA-binding protein that recruits the Tup1-Ssn6 complex and is responsible for repressing hypoxia-induced genes (Holstege et al, 1998;Becerra et al, 2002). Previous work designed to dissect the mechanism of Tup1-mediated repression has concentrated mainly on the analysis of a few Tup1-repressed genes and reporter constructs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, by phosphorylating the C-terminal domain of the largest subunit of RNA polymerase II, it can inactivate the holoenzyme, as assayed in vitro, and thus has been proposed to play a negative role in transcription (26). Deletion of Srb10͞11 or Srb7 has been reported to decrease Tup1-mediated repression and TUP1 has recently been reported to interact with Srb7 (23,27,28).…”
mentioning
confidence: 99%